Recurrent cutaneous abscesses in two Italian family members - Carmen Cantisani; Antonio Richetta; Andrea Bitonti; Pietro Curatolo; Gianfranco Ferretti; Carlo Mattozzi; Luca Melis; Emidio Silvestri; Stefano Calvieri (MDPI AG, 2010)
Environmental mycobacteria are the causative factors of an increasing number of infections worldwide. Cutaneous infections as a result of such mycobacteria are often misdiagnosed, and their treatment is difficult since they can show in vivo and in vitro multidrug resistance. Absence of pathognomonic clinical signs and variable histological findings often delay diagnosis. We report a case of localized recurrent soft tissue swelling by Mycobacterium marinum in 2 members of the same family. The cases are being reported for their uncommon clinical presentation and the associated etiological agent. Patients recovered completely following therapy with rifampicin 600 mg plus isoniazide 300 mg daily for 45 days.